Initial Validation of a School Counselor Accountability Scale (ID-SCAS) Using The Rasch Model - Binti Isrofin; Agus Taufiq; Ahman; Nila Zaimatus Septiana; Yuli Nurmalasari (Universitas Negeri Semarang, 2024)
School counseling accountability has transformed from simply counting counselor activity to being data and evidence-based to demonstrate impact on student success. However, few accountability scales have been developed specifically for school counselors. This study aims to test the reliability and validity of the school counselor accountability scale using the Rasch model. The scale developed included six key indicators: aligning the mission of the counseling program with the school mission (mission), ), identify critical student data (element), analyzing data (analysis), uniting with stakeholders to plan action (stakeholder unite), collecting results (result), and reporting results (educate). This study involved an initial sample of 78 Semarang city school counselors who are members of the Consultation of Guidance and Counseling Teachers (MGBK). The results of the analysis showed that the item reliability index on the accountability scale reached 0.88, while the respondent reliability was 0.97, with a Cronbach's alpha value of 0.98, indicating very high internal consistency. In addition, the unidimensionality test showed that the variance explained by the model was 39%, well above the minimum threshold of 20%, indicating that the scale is able to measure one clear construct. Thus, this initial test shows that the school counselor accountability scale has good reliability and validity and is ready to be used in the measurement of school counselor accountability. Akuntabilitas konseling sekolah telah bertransformasi dari sekadar menghitung aktivitas konselor menjadi berbasis data dan bukti untuk menunjukkan dampak pada keberhasilan siswa. Skala akuntabilitas yang telah dikembangkan secara khusus untuk konselor sekola masih belum banyak. Penelitian ini bertujuan untuk menguji reliabilitas dan validitas skala akuntabilitas konselor sekolah menggunakan model Rasch. Skala yang dikembangkan mencakup enam indikator utama: menyelaraskan misi program BK dengan misi sekolah (mission), mengumpulkan data kinerja siswa (element), menganalisis data (analysis), bersatu dengan pemangku kepentingan untuk merencanakan tindakan (stakeholder unite), mengumpulkan hasil (result), dan melaporkan hasil (educate). Penelitian ini melibatkan sampel awal sebanyak 78 konselor sekolah kota Semarang yang tergabung dalam Musyawarah Guru Bimbingan dan Konseling (MGBK). Hasil analisis menunjukkan bahwa indeks reliabilitas item pada skala akuntabilitas mencapai 0,88, sedangkan reliabilitas responden sebesar 0,97, dengan nilai Cronbach's alpha 0,98, yang mengindikasikan konsistensi internal yang sangat tinggi. Selain itu, uji unidimensionalitas menunjukkan bahwa varians yang dijelaskan oleh model sebesar 39%, jauh di atas ambang batas minimum 20%, yang menunjukkan bahwa skala ini mampu mengukur satu konstruksi yang jelas. Dengan demikian, tes awal ini menunjukkan bahwa skala akuntabilitas konselor sekolah memiliki reliabilitas dan validitas yang baik serta siap untuk digunakan dalam pengukuran akuntabilitas konselor sekolah.